Insurance policy and cropping structure adjustment toward staple grains in China: implications for food system resilience and security - Wang, Jiawei; Yuan, Zihui; Wu, Zhihua; Kuang, Xia; Ye, Feng (Frontiers in Nutrition, 2025)
IntroductionThe ongoing decline in staple crop acreage and the accelerating trend of “non-grain” cultivation pose structural risks to China’s food security. Agricultural insurance, beyond its traditional role in risk mitigation, may serve as a structural policy tool to influence farmers’ planting decisions and guide cropping structures toward staple grains. However, empirical evidence on this guiding function remains limited.MethodsDrawing on data from the 2020 China Rural Revitalization Survey (CRRS), this study employs a two-limit Tobit model to examine the impact pathways and moderating mechanisms through which agricultural insurance affects farmers’ cropping structure adjustment. The analysis addresses endogeneity issues and explores heterogeneous effects across different farmer groups.ResultsAgricultural insurance significantly increases the proportion of staple crops in total cultivated area, with findings robust to both robustness checks and endogeneity tests. Mechanism analysis shows that digital technology training significantly strengthens the incentive effect by improving farmers’ ability to access and interpret policy information. The marginal effect also rises with greater distance from the administrative center, indicating higher responsiveness in institutionally underserved areas. Heterogeneity analysis reveals stronger effects among highly educated farmers, small-scale operators, residents in pilot regions, those in non-plain terrains, and farmers in eastern provinces.DiscussionThese results confirm the effectiveness of agricultural insurance as a policy instrument for guiding cropping structure adjustments. Strengthening policy communication, expanding service coverage—especially in remote areas—and improving coverage levels can further enhance its contribution to national food security strategies and the Sustainable Development Goals (SDGs).